The Development Of Online Quizzes Using The Quizziz Application On Bacterial Material - Alfi Ainun Oktafianti; Fatikhatun Nikmatus Sholihah; Rossanita Truelovin Hadi Putri (SCHOOLAR: Social and Literature Study in Education, 2024)
Education in the 5.0 era is related to the availability of digital infrastructure. Learning media that is in accordance with the 5.0 era uses multimedia technology such as video, audio, images, animation, and games. One of them uses Quizziz. The purpose of this study is to describe the feasibility of online quiz questions using the Quizziz application on bacterial material based on the validation results of assessment experts, material experts, and student responses. This research is a development research using a 4D development model without dessiminate. Data collection instruments in the form of validation sheets and response questionnaires. Data collection in the form of questionnaires, validation and student responses. Eligibility is measured using validity tests by assessment expert validators and material expert validators. The results showed that the online quiz questions based on the assessment of expert assessment validators obtained a score of 78.57%. which means it is valid and the material expert validator obtained a value of 89.28% which means it is very valid. While the results of student responses from this study showed that online quiz questions based on student response questionnaires obtained a score of 97.57%. which means it is very interesting